Effects of tele-rehabilitation mental practice on balancing performance of patients with hemiplegia - Kim So Yeon; Park Su Jin; Lee Ye Eun; Lee Eun Ha; Lim Hwa Yeong; Lim Hwa Yeong; Yoo Gyu (Sciendo, 2018)
Study aim: The purpose of this study was to confirm the effectiveness of tele-rehabilitation mental practice (TRMP) on balancing performance for patients with hemiplegia. Material and methods: This study included five stroke patients, and all participants were trained to help to recover balancing performance. TRMP was applied for a total of 15 training sessions for 3 weeks, and pre- and post-intervention evaluations were carried out during this study. The Berg Balance Scale was used to confirm the balance ability, the Modified Falls Efficacy Scale to confirm the falls efficacy, and the Wii program to confirm the right and left weight distribution ratio. Results: As a result of this study, we could not confirm a significant difference between pre- and post-intervention balance capacity and fall efficacy. However, weight distribution showed a significant difference after the intervention. Conclusion: TRMP may be applied in novel balance training for stroke patients.